PURIFICATION OF BIODIESEL FROM USED COOKING OIL FOR SULFUR AND PHOSPHORUS REMOVAL - ELLANGOVAN, RUBAGANESH (IRC, 2019)
Biodiesel has attracted worldwide attention due to its potential of replacing fossil-based fuel as an economical and environmental decision. However, biodiesel tend to contain high amount of impurity and needs to undergo various purification process before being used in a vehicle engine. Therefore, standards were set before biodiesel is used for combustion. In order to conform the stringent international standard, the purification process is an essential section in the overall process. This research focused on the removal of Phosphorous and Sulphur removal from used cooking oil biodiesel. Generally, degumming method is used for phosphorous removal and hydrodesulfurization method is practised for sulphur removal. However, this research field has not been investigated thoroughly in term of water weight percent to Phosphorus removal reaction for degumming method and adsorption method using mixture of CuZeolite and Activated Carbon adsorbent for sulphur removal method with varying weight percent of Activated carbon to CuZeolite.